A case for contemporary third literature: the black experience in the postmillennial fiction of three Kwela authors - Mthembu, Lumumba (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
This study seeks to uncover the manner in which the young black experience is constructed in three novels by Sifiso Mzobe, Kgebetli Moele and K. Sello Duiker. Young Blood, Untitled and Thirteen Cents all feature teenage narrators navigating the social milieu of South Africa in the twenty-first century. My analysis is informed by Frantz Fanon's postcolonial theory because South Africa's socio-economic landscape conforms to the divisions laid out in The Wretched of the Earth. I contend that post-apartheid South Africa is developing in a manner that is symptomatic of the Fanonian post-independence African state. My close reading of the novels teases out the conditions under which young black subjects must survive and express themselves. I look into the roles of the community, the government, the family, and the school in shaping this experience. Naturally, my discussion segues into questions of sexuality and gender as they intersect with race. I demonstrate how these texts fail and succeed as works of Third Literature, a genre derived from Third Cinema, which I have adapted due to its Fanonian ideological underpinning. Third Literature is a fundamentally revolutionary and activistic genre which seeks to pave the way for social change. In this regard, I concern myself with the recommendations these three authors may have for the readers of their texts. In conclusion, these texts demonstrate that racialized identities are social constructs with measurable experiential effects. However, there are ways of actively resisting or even
Keywords: Uncatalogued